Taming the Beast: Harnessing Blockchains in Developing Country Governments - Zambrano, Raúl (Frontiers in Blockchain, 2020)
Amid pressing demands to tackle critical sustainable development goals, governments in developing countries face the additional complex task of embracing new digital technologies such as blockchains. This paper takes a conceptual approach and presents a framework that interlinks development, technology, and governments while highlighting the relevance of state capacity and democratic governance in such dynamics. With this in hand, blockchain technology is revisited from the perspective of governments in the Global South, identifying in the process key traits and presenting a new typology. Research gaps regarding the relationship between this technology and both development and developing country government are also identified. A closer look at some on the ground blockchain implementations yields some early evidence on the advantages and risks involved in the process. The paper closes with a discussion of the results within the proposed framework suggesting additional research themes. It also provides some basic guidance for development practitioners interested in enhancing current programs using blockchains as an enabler.